Branding and Marketing Strategies of Dokkho Solutions Ltd. in helping recruiting agencies with recruitment leveraging through technology - Khan, Zahidur Rahim (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.